2020
DOI: 10.1007/978-3-030-59725-2_38
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Detection of Fetal Pose in 3D MRI by Deep Reinforcement Learning with Physical Structure Priors on Anatomy

Abstract: Fetal MRI is heavily constrained by unpredictable and substantial fetal motion that causes image artifacts and limits the set of viable diagnostic image contrasts. Current mitigation of motion artifacts is predominantly performed by fast, single-shot MRI and retrospective motion correction. Estimation of fetal pose in real time during MRI stands to benefit prospective methods to detect and mitigate fetal motion artifacts where inferred fetal motion is combined with online slice prescription with low-latency de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Salehi et al trained regression CNNs to estimate the 3D positions of the fetal brain using individual slices and also provided a fast SVR strategy [31]. Zhang et al employed an end-to-end and multi-agent deep reinforcement learning network to detect the landmarks of the fetal pose in each time frame [32].…”
Section: A Related Workmentioning
confidence: 99%
“…Salehi et al trained regression CNNs to estimate the 3D positions of the fetal brain using individual slices and also provided a fast SVR strategy [31]. Zhang et al employed an end-to-end and multi-agent deep reinforcement learning network to detect the landmarks of the fetal pose in each time frame [32].…”
Section: A Related Workmentioning
confidence: 99%
“…4 To further improve motion robustness, reduced FOV (rFOV) fetal brain imaging could substantially reduce acquisition time because the region of interest (ROI), the fetal brain slice, occupies only a small fraction of the gravid abdomen and requires many fewer phase-encoding to fully sample. With fast fetal brain tracking and pose estimation techniques, 5,6 2D spatially selective pulses could excite a slice restricted to the fetal brain in real time.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have shown that, given a series of annotated images, the agent can learn the best path to converge to the marked position. In response to the issue of artifacts in 3D fetal MRI images, Zhang et al [13] deployed 15 agents based on DRL, simultaneously detecting 15 feature markers, and set additional rewards based on the distance between the agent and the fetal body nodes to improve detection accuracy. Pesce et al [14] studied how to locate lung lesions on chest radiographs.…”
Section: Introductionmentioning
confidence: 99%